Public Employment Services, and Activation Policies - Kuddo, Arvo (World Bank, Washington, DC, 2013)
One of the responses to new challenges in the labor market has been the development and expansion of employment services and active labor market policies based on activation principles. The objective of this study is to document and review international experiences, predominantly from selected emerging market economies and developing countries, with the design and implementation of activation programs, provided by Public Employment Services, through the prism of incentives and sanctions. Employment promotion legislation from the reviewed countries is a major source of information. Participation of beneficiaries in relevant services and programs is also analyzed. The study finds that the countries use a variety of instruments, be it specific employment services, active labor market programs, or benefit and other sanctions, to 'activate' jobseekers with an aim to encourage them to become more active in their efforts to find work and/or improve their employability. In practice, the activation policies vary considerably across countries.